Substantiation of selection of components at creation of thermal insulating dry building mixtures - I. Loganina, V.; V. Frolov, M.; P. Skachkov, Yu. (International Journal of Engineering and Technology, 2018)
The possibility of reducing the thermal conductivity of heat-insulating finishing coatings using as a filler ash microspheres of aluminosilicate and glass hollow microspheres is substantiated. A mechanism of heat transfer through heat-insulating composites is considered, depending on the type of filler used. It is revealed that the ability of the finishing coat to reflect heat does not depend on the type of filler used. It is established that the convective component of heat transfer does not significantly influence the heat-shielding qualities of the finishing coatings under consideration.Â